TREATMENT OF PROGRESSION OF DIFFUSE ASTROCYTOMA BY HERBAL MEDICINE: CASE REPORT - TrogrliÄ‡, Ivo; TrogrliÄ‡, Dragan; TrogrliÄ‡, Zoran (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The paper presents the results of the use of phytotherapy in a 33-year-old woman who, after finishing the oncological treatment of diffuse astrocytoma, had tumour progression. Material and methods: Phytotherapy was introduced after the tumour had progressed. It consisted of 4 types of herbal medicine which the subject was taking in form of tea once a day at regular intervals. The patient started phytotherapy along with temozolomide, which was the only oncological treatment she was under after the tumour had progressed. Following the finished chemotherapy, the patient continued the treatment with herbal medicine only. She regularly took phytotherapy without interruption and to the fullest extent for 30 months, and the results of treatment were monitored by periodic scanning using nuclear magnetic resonance technique. Results: The control scanning that was conducted after the end of combined treatment with temozolomide and phytotherapy showed tumour regression. The patient continued with phytotherapy after finishing chemotherapy and, during the following 24 months, it was the sole treatment option. In that period, the regression of the tumour continued, until a control examination 30 months after the introduction of phytotherapy showed no clinical and radiological signs of tumour. Conclusion: The results presented in this research paper clearly indicate the potential of phytotherapy in the treatment of some types of brain tumours. A complete regression of tumour following the treatment with nothing but herbal medicine offers support for such claim. Future research should demonstrate the effectiveness of phytotherapy, as a supplementary form of brain tumour treatment, and the results of this research should be compared with the existing information on the effectiveness of the protocols currently used in the treatment of these types of tumour.